Adverse events of nucleos(t)ide analogues for chronic hepatitis B: a systematic review - de Fraga, Raquel Scherer (J Gastroenterol, 2020)
Nucleos(t)ide analogues (NAs) are the main drug category used in chronic hepatitis B (CHB) treatment. Despite the fact that NAs have a favourable safety profile, undesired adverse events (AEs) may occur during the treatment of CHB. Given the eminent number of patients currently receiving NAs, even a small risk of any of these toxicities can represent a major medical issue. The main objective of this review was to analyse information available on AEs associated with the use of NAs in published studies. We choose the following MesH terms for this systematic review: chronic hepatitis B, side effects and treatment. All articles published from 1 January 1990 up to 19 February 2018 in MEDLINE of PubMed, EMBASE, the Cochrane Library and LILACS databases were searched. A total of 120 articles were selected for analysis, comprising 6419 patients treated with lamivudine (LAM), 5947 with entecavir (ETV), 3566 with tenofovir disoproxil fumarate (TDF), 3096 with telbivudine (LdT), 1178 with adefovir dipivoxil (ADV) and 876 with tenofovir alafenamide (TAF). The most common AEs in all NAs assessed were abdominal pain/discomfort, nasopharyngitis/upper respiratory tract infections, fatigue, and headache. TAF displays the highest density of AEs per patient treated among NAs (1.14 AE/treated patient). In conclusion, treatment of CHB with NAs is safe, with a low incidence of AEs. Despite the general understanding TAF being safer than TDF, the number of patients treated with TAF still is too small in comparison to other NAs to consolidate an accurate safety profile. PROSPERO Registration No. CRD42018086471